War over words :censorship in India, 1930-1960 - Devika Sethi (CUP, 2019)
"Censorship has been a universal phenomenon through history. However, its rationale and implementation has varied, and public reaction to it has differed across societies and times. This book recovers, narrates, and interrogates the history of censorship of publications in India over three crucial decades - encompassing the Gandhian anti-colonial movement, the Second World War, Partition, and the early years of independent India. In doing so, it examines state policy and practice, and also its subversion, in a tumultuous period of transition from colonial to self-rule in India"--